[PP.37.03] IMPACT OF SEASONALITY AND AIR POLLUTANTS ON WAVE REFLECTION IN HYPERTENSIVE PATIENTS. (September 2016) - Di Pilla, M.; Bruno, R.M.; Ghiadoni, L.; Stea, F.; Massetti, L.; Bertolozzi, I.; Taddei, S.; Modesti, P.A.
Abstract : Objective: Important climate-related variations of clinic and ambulatory blood pressure (BP) have been repeatedly reported. However, the influence of seasonality and other environmental factors such as air pollutants and outdoor temperature on wave reflection, a parameter associated with increased risk of cardiovascular events, has never been investigated. The aim of the present study was to examine in a cross-sectional survey whether acute variations in these environmental factors may affect wave reflection, measured as augmentation pressure (AP) and augmentation index normalized at a heart rate of 75bpm (AIx75). Design and method: This survey included retrospectively 731 hypertensive patients (30–88 years, 417 drug-treated), referring to our Hypertension Center during a 5-year period (2006–2011). Radial arterial tonometry was performed to all participants in a quiet, temperature-controlled (22–24°C) room, with the calculation of central BP, Aix75 and AP. The data of the local office of the National Climatic Data Observatory were used to estimate meteorological conditions and air pollutants (PM10, O3, CO, N2O) exposure the same day of the vascular evaluation. Results: Aix75 (mean value 24.1 ± 10.2%) was related to age (r = 0.27, p < 0.001), BMI (r = −0.12, p = 0.002), central systolic BP (r = 0.32, p < 0.001), diastolic BP (r = 0.14, p < 0.001), total cholesterol (r = 0.16, p < 0.001), LDL (r = 0.08, p = 0.04), HDL (r = 0.26, p < 0.001), creatinine (r = −0.15, p < 0.001). No significant correlation was found between AIx75 and environmental factors (daylight hours, mean temperature and air pollutants). The multiple regression analysis including the above-mentioned variables confirmed an independent association of AIx75 only with age, central systolic BP, diastolic BP and female sex. This result was confirmed also in the untreated group. Furthermore, no significant correlation was found between AP (mean value 14.2 ± 7.9 mmHg) and daylight hours, mean temperature and air pollutants, neither in the univariate analysis, nor in the multiple regression analysis adjusted for confounders. Conclusions: This cross-sectional analysis suggests that seasonality, expressed by the daily number of hours of light, and acute changes in environmental factors such as outdoor temperature and air pollutants concentration, do not influence either AP or AIx75.